if h(x)=7-3x find in simplest form h(2x-1) I've tried subbing them into each other but I can't get the right answer.
Follow Math Help Forum on Facebook and Google+
Originally Posted by lucymm if h(x)=7-3x find in simplest form h(2x-1) I've tried subbing them into each other but I can't get the right answer. h(2x - 1) = 7 - 3(2x - 1) now simplify
Originally Posted by lucymm if h(x)=7-3x find in simplest form h(2x-1) I've tried subbing them into each other but I can't get the right answer. h(x) = 7-3x h(2x-1) = 7-3(2x-1) = 7-6x+3 = -6x+10 or -2(3x-5) or 2(-3x+5) ... etc
View Tag Cloud